Improving Mathematics Learning Outcomes on Fraction Material through a Realistic Mathematics Approach for Elementary School Students - Labiibah Shafiyyah Yaasmin (Yayasan Insan Mulia Bima, 2024)
Facing the era of globalization which is accompanied by the very rapid development of science and technology, a person is required to be able to utilize information well and quickly so that high human resources are needed, one of which is in the field of mathematics. Observations at Attarbiyah Elementary School found the problem of low learning outcomes in mathematics lessons on fractions for grade 4 students at Attarbiyah Elementary School, Surabaya under the Maximum Completeness Criteria, namely 80. The aim of this research was to improve mathematics learning outcomes on fractions. This research is Classroom Action Research which was carried out in two cycles. The results of research on improving the learning outcomes of 4th grade students at Attarbiyah Elementary School, Surabaya after implementing a realistic mathematics approach were declared successful, this was proven because there was an increase in the average learning outcomes in each cycle, namely cycle I and cycle II. In cycle I, the average student learning result was 70.85% and in cycle II it increased to 88.85%. Applying a realistic mathematical approach can improve student learning outcomes in mathematics lessons regarding fractions.